The Effect Of Problem-Based Learning on Middle School Students' Environmental Literacy and Problem-Solving Skills - Gülsüm Gök; Gökçe Boncukçu (Universitas Pendidikan Indonesia, 2023)
This study investigates the impact of the problem-based learning (PBL) model on middle school students' environmental literacy and problem-solving skills. A quantitative research study was conducted using a quasi-experimental design for this aim. The sample comprises 114 8th-grade students from a public middle school in Şanlıurfa, Turkey. Four intact classes were randomly assigned to experimental and control groups and instructed in sustainable development using the PBL model and curriculum-based instruction, respectively. Data were collected through the Environmental Literacy Questionnaire and the Problem Solving Skill Test and analyzed using Mixed-Between-Within ANOVA (Mixed-ANOVA) to assess the effectiveness of the instructional methods. The results revealed that PBL was more effective in developing environmental attitudes than curriculum-based instruction. However, it did not produce the same effect on environmental behavior. Furthermore, it can be asserted that PBL significantly enhanced students' problem-solving skills in the experimental group, while the scores of students in the control group remained unchanged. The implications of these findings were discussed. Given its positive outcomes, PBL is recommended for cultivating students with the requisite skills to become responsible citizens who can take action on environmental issues